Preparation method of monodisperse nano beryllium oxide
Through the sol-gel method, a three-dimensional network structure is formed in the solution using urea and formaldehyde aqueous solutions and acrylic polymers to form a three-dimensional network structure, which wraps water-soluble beryllium salt ions, and solves the problems of complex and high cost of nano beryllium oxide processes in the existing technology, realizing the Preparation of nanoberyllium oxide with uniform particle size and safe particle size.
Patent Information
- Application Number
- CN202411542064.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the nano-scale beryllium oxide preparation process is complex, the cost is high, and the reagents used have safety risks and insufficient particle size uniformity, making it difficult to meet the needs of industrial large-scale production.
By using the sol-gel method, urea and formaldehyde aqueous solution were mixed, hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate and polyethylene glycol bisacrylate were added to adjust the pH value, and the pH was added. Water-soluble beryllium salt and an inert atmosphere slowly heat up to form a gel precursor, which is then dried and calcined to form a monodispersed nanoberyllium oxide.
The preparation of nanoberyllium oxide with uniform particle size is achieved, which reduces production costs, simplifies the process flow, avoids the use of toxic reagents, and improves the safety and particle size dispersion of the product.
Smart Images

Figure CN119263315A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of beryllium oxide preparation, and in particular relates to a method for preparing monodisperse nanometer beryllium oxide. Background Art
[0002] Beryllium oxide has the characteristics of high thermal conductivity, high melting point, high strength, high insulation, low dielectric constant, and low grafting loss. It is used in many fields such as microwave technology, electronic information, nuclear industry, and optoelectronics. In the past, the existing technology was mostly used to manufacture micron-level beryllium oxide, but with the development of current science and technology, the demand for nano-level beryllium oxide has gradually increased, especially nano-level beryllium oxide materials with uniform particle size dispersion are very popular in the market. There are mainly deposition method, emulsion method, and sol-gel method to manufacture nano-level beryllium oxide, but there is often a problem of insufficient uniformity in particle size dispersion.
[0003] The inventor's previous patent CN116553583A discloses a method for preparing nano-beryllium oxide, which includes the following steps: S1. Preparation of beryllium hydroxide suspension: stirring and adding organic amine to a beryllium sulfate aqueous solution, controlling the pH value of the suspension, continuing stirring, and standing for aging to obtain a suspension; S2. Preparation of beryllium hydroxide gel: stirring the suspension evenly, filtering, and washing to obtain a gel; S3. Hydrothermal pretreatment of the beryllium hydroxide gel: dissolving the gel in deionized water, adding high molecular compounds with different polymerization degrees and ammonium persulfate, stirring evenly, ultrasonically treating, and transferring the mixed solution to a hydrothermal synthesis reactor; S4. Hydrothermal treatment: controlling the hydrothermal synthesis temperature and reaction time; S5. Formation of nano-beryllium oxide: after the hydrothermal treatment is completed, the mixed solution is filtered and washed, and the obtained solid material is dried and roasted to obtain a nano-beryllium oxide material. This patent uses polymer compounds with different polymerization degrees, and uses high-polymer compounds to form stable three-dimensional network structure polymer chains, while low-polymer compounds are conducive to optimizing dispersion performance, making the molecular chains in the three-dimensional structure easy to stretch, so that the beryllium oxide grains are not easy to aggregate, and the final nano-beryllium oxide particle size distribution is more uniform. CN116239133A discloses a method for preparing beryllium oxide, comprising the following steps: (1) premixing: mixing beryllium salt with a low eutectic solvent to obtain a mixture A; (2) ionic liquid coating: mixing the mixture A in step (1) with an ionic liquid to obtain a mixture B; (3) carbonization: carbonizing the mixture B obtained in step (2); (4) calcining: calcining the carbonized product in step (3) to obtain beryllium oxide. The present invention can "bring closer" the coating effect of the beryllium salt and the outermost ionic liquid through the pre-coating of the low eutectic solvent, thereby improving the interaction force between the beryllium salt, the low eutectic solvent and the ionic liquid, so that the ionic liquid is coated more tightly and the particle size range of the beryllium oxide is reduced. CN114671444A discloses a beryllium oxide and a preparation method thereof, comprising the following steps: (1) mixing the beryllium salt and the ionic liquid, and coating the ionic liquid on the surface of the beryllium salt to obtain a mixture; (2) carbonizing the mixture to obtain a beryllium salt coated with a carbon layer; (3) calcining the beryllium salt coated with the carbon layer to obtain beryllium oxide with a small particle size and a concentrated particle size distribution, which not only prevents the aggregation of nanoparticles, but also reduces the thermal decomposition temperature of the precursor beryllium salt, further reducing the production cost. The above patents all prepare nano-scale beryllium oxide with different degrees of monodispersion. However, the preparation process is complicated and costly, and reagents such as ionic liquids are used, which still needs to be improved in industrial large-scale production.
[0004] The prior art also prepares nano-sized beryllium oxide by the sol-gel method, which is mostly acrylamide polymers. The three-dimensional network structure of polyacrylamide formed after polymerization separates and blocks the ions in the solution, and obtains a gel containing a salt solution in a small space unit. After drying and calcination, nano powders can be obtained. However, its acrylamide is neurotoxic and there are still certain safety risks in large-scale industrial production; and after experiments, although nano-sized beryllium oxide can be obtained, the uniformity of the particle size needs to be improved. Therefore, it is necessary to develop a simple, low-cost, green and environmentally friendly production method with low toxicity for the preparation of monodispersed nano-sized beryllium oxide. Summary of the invention
[0005] In order to solve the defects of the prior art that the preparation process of monodisperse nano-sized beryllium oxide is complicated and the cost is high. The present invention provides a method of using a sol-gel method to synthesize two different types of polymers, which cooperate with each other, so as to prepare nano-sized beryllium oxide with uniform particle size at low cost and simple operation. To achieve the above purpose, the present invention provides the following technical solutions:
[0006] A method for preparing monodisperse nano-beryllium oxide comprises the following steps:
[0007] (S1) urea and formaldehyde aqueous solution are mixed uniformly, the pH is adjusted to be weakly alkaline with an organic amine, and hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate and polyethylene glycol diacrylate are added to obtain a premixed solution;
[0008] (S2) adding a water-soluble beryllium salt to the premixed solution, adding a water-soluble initiator under an inert atmosphere, and slowly heating the temperature to 60-80° C. to react to obtain a gel precursor;
[0009] (S3) After the gel precursor is dried, it is calcined, washed, and filtered to obtain monodispersed nano-beryllium oxide.
[0010] Furthermore, in step (S1), the concentration of the formaldehyde aqueous solution is 20-40wt%, such as 37wt%; the organic amine is selected from at least one of isopropylamine, n-butylamine, cyclohexylamine, diethylamine, triethylamine, diethylmethylamine, diethylisopropylamine, and diethylenetriamine, and the weak alkalinity is adjusted to a pH of 8-9.
[0011] Furthermore, in step (S1), the hydroxyalkyl (meth)acrylate is selected from at least one of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; the C12-16 alkyl (meth)acrylate is selected from at least one of dodecyl (meth)acrylate, tetradecyl (meth)acrylate, and hexadecyl (meth)acrylate; and the number average molecular weight of the polyethylene glycol segment in the polyethylene glycol diacrylate is 200-400.
[0012] Furthermore, in step (S1), the molar ratio of urea to formaldehyde is 1:2-2.5; the molar ratio of urea, hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate and polyethylene glycol diacrylate is 1:0.6-0.8:2.2-3.4:0.2-0.3.
[0013] Furthermore, in step (S2), the water-soluble beryllium salt is selected from at least one of beryllium sulfate, beryllium chloride and beryllium nitrate; and the amount of water-soluble beryllium salt added is such that the Be concentration in the system is 1-2 mol / L.
[0014] Furthermore, in step (S2), the inert atmosphere is at least one of nitrogen, helium, and argon; the water-soluble initiator is at least one of ammonium persulfate, potassium persulfate, and sodium persulfate. The amount of the water-soluble initiator added is 1-3wt% of the total mass of hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate, and polyethylene glycol diacrylate; and the slow heating is controlled at a heating rate of 1-3°C / min.
[0015] Furthermore, in step (S3), drying is not particularly limited, such as vacuum drying. Calcination is performed by heating the temperature to 600-1000°C at a heating rate of 1-5°C / min and keeping the temperature for 5-10 hours. Washing is performed by washing with ethanol and deionized water alternately. During calcination, the heating rate should not be too high, otherwise carbonization is likely to occur.
[0016] The present invention adopts a sol-gel method with simple process and low cost. The hydroxymethyl urea produced by urea and formaldehyde and the acrylic acid derivative monomer are polymerized simultaneously under heating initiation conditions. The two polymers are entangled with each other to form a three-dimensional network polymer structure. 2+ and SO4 2- Ion encapsulation, as the polymerization continues, all ions in the solution are separated into small units separated by the three-dimensional network structure formed by the two polymers, and then dried and calcined. During the calcination process, the polymers in the three-dimensional network structure will also undergo thermal decomposition, preventing the agglomeration of beryllium oxide particles. The resulting beryllium oxide is nanoscale and has a monodisperse particle size. When preparing a polymer network, it is necessary to control the monomer concentration ratio to obtain a dense polymer three-dimensional network, which directly affects the particle size and particle size dispersity of the resulting beryllium oxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the SEM image of beryllium oxide obtained in Example 1.
[0018] Figure 2 This is the SEM image of beryllium oxide obtained in Comparative Example 1. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with specific examples, but the present invention is not limited to the following examples.
[0020] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0021] Example 1
[0022] (S1) 1 mol of urea and 37 wt % formaldehyde aqueous solution (the amount of formaldehyde substance is 2.2 mol) are mixed uniformly, the pH is adjusted to 8.5 with triethylamine, 0.8 mol of hydroxyethyl methacrylate, 3.4 mol of dodecyl methacrylate and 0.2 mol of polyethylene glycol diacrylate (PEG segment number average molecular weight 400) are added to obtain a premixed solution;
[0023] (S2) beryllium sulfate is added to the premixed solution to make the Be concentration in the system 1 mol / L, and ammonium persulfate is added in a nitrogen atmosphere, the amount of ammonium persulfate added is 1wt% of the total mass of the monomers, and the monomers are the sum of hydroxyethyl methacrylate, dodecyl methacrylate and polyethylene glycol diacrylate, and the temperature is raised to 70°C at a heating rate of 2°C / min for 4 hours to obtain a gel precursor;
[0024] (S3) After the gel precursor is dried under vacuum, the temperature is increased to 850°C at a heating rate of 5°C / min and kept at this temperature for 10 h. The gel precursor is washed alternately with ethanol and deionized water for three times, filtered, and dried under vacuum to obtain monodisperse nano-beryllium oxide.
[0025] Example 2
[0026] Other conditions were the same as those in the operation and Example 1, except that in step (S1), the acrylic monomer was replaced with 0.6 mol hydroxybutyl methacrylate, 2.2 mol hexadecyl methacrylate and 0.3 mol polyethylene glycol diacrylate (PEG segment number average molecular weight 200).
[0027] Example 3
[0028] The other conditions are the same as those in the operation and Example 1, except that in step (S2), the amount of ammonium persulfate added is 3 wt% of the total weight of the monomers.
[0029] Example 4
[0030] The other conditions are the same as those in the operation and Example 1, except that in step (S3), the temperature is increased to 1000°C at a heating rate of 5°C / min.
[0031] Example 5
[0032] The other conditions are the same as those in the operation and Example 1, except that in step (S3), the temperature is increased to 600°C at a heating rate of 5°C / min.
[0033] Comparative Example 1
[0034] Other conditions were the same as those in operation and Example 1, except that in step (S1), hydroxyethyl methacrylate was replaced with an equimolar amount of ethyl methacrylate.
[0035] Comparative Example 2
[0036] The other conditions were the same as those in the operation and Example 1, except that in step (S1), dodecyl methacrylate was replaced by an equimolar amount of hexyl methacrylate.
[0037] Comparative Example 3
[0038] The other conditions are the same as those in the operation and Example 1, except that in step (S1), polyethylene glycol diacrylate is replaced by an equimolar amount of diethylene glycol diacrylate.
[0039] Comparative Example 4
[0040] The other conditions are the same as those in the operation and Example 1, except that in step (S1), polyethylene glycol diacrylate is not added.
[0041] Comparative Example 5
[0042] Other conditions are the same as those in the operation and Example 1, except that in step (S1), urea and formaldehyde aqueous solution are not added, and the monomer is directly added to deionized water with an equal volume to the formaldehyde aqueous solution.
[0043] Comparative Example 6
[0044] The other conditions are the same as those in the operation and Example 1, except that in step (S1), no acrylic monomer is added, that is, no hydroxyethyl methacrylate, dodecyl methacrylate and polyethylene glycol diacrylate are added.
[0045] The homogeneous particle size D50 is tested by electron microscope photos using Nano Measure software, and the particle size distribution index is calculated by the formula D90-D10 / D50. BET The particle size distribution index D90-D10 / D50 is not a good indicator of particle size uniformity, which is closely related to the selected SEM image. BET / D50, also used as an indicator of particle size distribution, the results are shown in Table 1 and Figure 1 and Figure 2 shown.
[0046] Figure 1is a SEM image of beryllium oxide obtained in Example 1; Figure 2 This is the SEM image of beryllium oxide obtained in Comparative Example 1.
[0047] Table 1 Beryllium oxide particle size and particle size distribution index
[0048] project Particle size D50(nm) Particle size distribution index <![CDATA[Particle size BET (nm)]]> <![CDATA[Particle size BET / Particle size D50]]> Example 1 14.3 1.42 19.4 1.36 Example 2 15.2 1.38 20.1 1.32 Example 3 13.2 1.45 18.0 1.36 Example 4 16.5 1.50 23.2 1.41 Example 5 12.7 1.44 17.1 1.35 Comparative Example 1 16.1 1.72 25.9 1.61 Comparative Example 2 16.3 1.42 21.4 1.53 Comparative Example 3 21.7 1.75 30.4 1.34 Comparative Example 4 23.1 2.18 34.6 1.50 Comparative Example 5 16.8 1.95 25.8 1.53 Comparative Example 6 37.2 1.73 47.9 1.29
[0049] From the data in Table 1, it can be seen that the particle size of the nano-beryllium oxide obtained by the preparation method of the present invention is less than 20nm, and the particle size dispersion is good. The inventor speculates that the present invention adopts a three-dimensional network structure surrounded by two different polymers to divide the ions in the solution into small units, which prevents the agglomeration of the beryllium oxide particles and maintains a good particle size uniformity during the subsequent drying and calcination process. If either of the two polymers is missing, the purpose of obtaining a small and uniform beryllium oxide particle size cannot be achieved.
Claims
1. A method for preparing monodisperse nano-beryllium oxide, characterized in that: The following steps are involved: (S1) urea and formaldehyde aqueous solution are mixed uniformly, the pH is adjusted to be weakly alkaline by organic amine, and hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate and polyethylene glycol diacrylate are added to obtain a premixed solution; the molar ratio of urea to formaldehyde is 1:2-2.5; the molar ratio of urea, hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate and polyethylene glycol diacrylate is 1:0.6-0.8:2.2-3.4:0.2-0.3; (S2) adding a water-soluble beryllium salt to the premixed solution, adding a water-soluble initiator under an inert atmosphere, and slowly heating the temperature to 60-80° C. to react to obtain a gel precursor; (S3) After the gel precursor is dried, it is calcined, washed, and filtered to obtain monodispersed nano-beryllium oxide.
2. The preparation method according to claim 1, characterized in that: In step (S1), the concentration of the formaldehyde aqueous solution is 20-40 wt %; the weak alkalinity is adjusted to a pH of 8-9.
3. The preparation method according to claim 1, characterized in that: In step (S1), the organic amine is selected from at least one of isopropylamine, n-butylamine, cyclohexylamine, diethylamine, triethylamine, diethylmethylamine, diethylisopropylamine and diethylenetriamine.
4. The preparation method according to claim 1, characterized in that: In polyethylene glycol diacrylate, the number average molecular weight of the polyethylene glycol segment is 200-400.
5. The preparation method according to claim 1, characterized in that: In step (S2), the water-soluble beryllium salt is selected from at least one of beryllium sulfate, beryllium chloride and beryllium nitrate.
6. The preparation method according to claim 1, characterized in that: The amount of water-soluble beryllium salt added is such that the Be concentration in the system is 1-2 mol / L.
7. The preparation method according to claim 1, characterized in that: In step (S2), the inert atmosphere is at least one of nitrogen, helium, and argon; and the water-soluble initiator is at least one of ammonium persulfate, potassium persulfate, and sodium persulfate.
8. The preparation method according to claim 1, characterized in that: In step (S2), the amount of water-soluble initiator added is 1-3 wt % of the total mass of hydroxyalkyl (meth)acrylate, C12-16 alkyl (meth)acrylate and polyethylene glycol diacrylate.
9. The preparation method according to claim 1, characterized in that: In step (S2), the slow heating is controlled at a heating rate of 1-3°C / min.
10. The preparation method according to claim 1, characterized in that: In step (S3), the calcination is carried out by heating the temperature to 600-1000°C at a heating rate of 1-5°C / min and keeping the temperature for 5-10h.
Citation Information
Patent Citations
Beryllium oxide and preparation method thereof
CN114671444A
Preparation method of beryllium oxide
CN116239133A
Cited By
Preparation method for monodisperse nanometer beryllium oxide
WO2026091774A1